Hepatocellular carcinoma presenting primarily as ovarian metastasis in Egyptian woman: a case report and literature review - Abd El hafez, Amal (International Journal of Medicine, 2014)
Metastatic spread of hepatocellular carcinoma (HCC) to the ovary is an extremely rare event especially if presented in absence of a known hepatic primary and/or in a living patient. Here, a case of metastatic HCC to the ovary is presented in 54-years living Egyptian female patient in whom the ovarian lesion was the primary presentation associated with elevated serum alpha-fetoprotein level. Ultrasonography revealed 2 two focal hepatic lesions. The diagnosis was based on the simultaneous presence of ovarian and hepatic lesions, bilaterality, the trabecular growth pattern, cytological features, presence of bile and Periodic acid Sciff-positive, diastase-resistant cytoplasmic granules on microscopic examination and immuno-histochemistry. Metastatic HCC must be included in the differential diagnosis of hepatoid and oxyphil cell tumors of the ovary. Keywords: Hepatocellular Carcinoma, Ovarian Metastasis, Hepatoid, Oxyphil, Immuno-histochemistry.